Just War Tradition and the Restraint of War : a Moral and Historical Inquiry. - Johnson, James Turner (Princeton : Princeton University Press, 2014)
In this volume, a sequel to Ideology, Reason, and the Limitation of War, James Turner Johnson continues his reconstruction of the history of just war tradition by analyzing significant individual thinkers, concepts, and events that influenced its development from the mid-eighteenth century to the present. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts.
Cover; Contents; Part 1. The Problem of Understanding Just War Tradition; Part 2. Rival Conceptions of War and Its Limits; Part 3. Modern War and Attempts at Restraint; Select Bibliography; Index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Just war doctrine; Guerre juste; HISTORY -- Military -- Other; TECHNOLOGY & ENGINEERING -- Military Science; Just war doctrine